EXPLORING THE IMPACT OF EXPERIENTIAL MARKETING, WORD-OF-MOUTH (WOM), AND PROMOTIONAL STRATEGIES ON USER LOYALTY TOWARDS THE TOKOPEDIA APP - Panjaitan, Raya; Manurung , Hiskia (Jurnal Manajemen dan Bisnis, 2021)
Drawing upon the dynamic interplay of experiential marketing, word of mouth, and promotional strategies within the realm of e-commerce, this study pivots on their collective influence on customer loyalty, particularly among Tokopedia app users at the Immigration Office in Medan. The phenomenon of increased online shopping among Indonesian public sector employees provides the backdrop against which this research unfolds, aiming to discern the potency of these marketing strategies in fostering loyalty. The research objectives include evaluating the impact of experiential marketing, understanding the role of electronic word of mouth, and assessing the efficacy of promotions in cultivating a loyal customer base. Findings indicate that experiential marketing significantly enhances customer loyalty, electronic word of mouth is a positive and significant loyalty driver, and promotional activities, while positive, show a less pronounced impact on loyalty. Contributions of this research are twofold: it extends academic perspectives on e-commerce loyalty in the context of Indonesian public sector employees and offers pragmatic insights for e-commerce platforms to refine their marketing strategies. By fortifying the customer experience and addressing service quality, Tokopedia can potentially amplify customer satisfaction and consolidate its user base's loyalty.